2011
DOI: 10.3390/ijerph8030830
|View full text |Cite
|
Sign up to set email alerts
|

Subjects Agree to Participate in Environmental Health Studies without Fully Comprehending the Associated Risk

Abstract: Recent advances in environmental health research have greatly improved our ability to measure and quantify how individuals are exposed. These advances, however, bring bioethical uncertainties and potential risks that individuals should be aware of before consenting to participate. This study assessed how well participants from two environmental health studies comprehended consent form material. After signing the consent form, participants were asked to complete a comprehension assessment tool. The tool measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…They knew that comprehension was going to be tested after a time delay. This likely added to the length of time spent reviewing the consent form compared to the earlier studies of Baren, McNutt, and Lee [3][5]. Among both research professionals and patients, next-day comprehension was better in subjects randomized to the interactive iPad consent form.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They knew that comprehension was going to be tested after a time delay. This likely added to the length of time spent reviewing the consent form compared to the earlier studies of Baren, McNutt, and Lee [3][5]. Among both research professionals and patients, next-day comprehension was better in subjects randomized to the interactive iPad consent form.…”
Section: Discussionmentioning
confidence: 94%
“…After providing information verbally to two samples of women, research assistants observed that over half of the women read their consent forms in thirty seconds or less before signing. Lee and colleagues gave 73 subjects a comprehension quiz right after the consent form was signed [5]. Of six elements of the form, about half the subjects were not aware of two or more study-related risks.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have raised the alarm that the consent process is “broken” (Hayden, 2012). For example, research has shown that patients have great difficulty understanding and recounting the research to which they have consented (Brehaut et al, 2012; Ghandour, Yasmine, & El-Kak, 2013; Lee, Lampert, Wilder, & Sowell, 2011; Tamariz, Palacio, Robert, & Marcus, 2013). In other words, clinicians are concerned that the informed consent process leaves research participants and patients not informed about how their data will be used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the consent process have likewise demonstrated poor participant understanding of study procedures and outcomes. 4,5 Further complicating the challenges to achieving informed consent, clinical studies and their accompanying consent processes have grown in complexity, particularly for multisite clinical trials.…”
mentioning
confidence: 99%